N6-Methyladenosine Methyltransferase METTL14-Mediated Autophagy in Malignant Development of Oral Squamous Cell Carcinoma - Wang, Fang; Zhu, Yue; Cai, Hongshi; Liang, Jianfeng; Wang, Wenjin; Liao, Yan; Zhang, Yadong; Wang, Cheng; Hou, Jinsong (Frontiers in Oncology, 2021)
N6-methyladenosine (m6A) is the most abundant internal mRNA modification in eukaryotes and is related to stability, localization, or translation efficiency in tumorigenesis. Autophagy plays an important role in the occurrence and development of tumours. However, the relationship between m6A and autophagy remains unclear. In this study, we used a rapamycin-induced autophagy model of oral squamous cell carcinoma (OSCC) cells, and observed increased m6A RNA methylation. When autophagy was activated, the methyltransferase-like 14 (METTL14) expression was upregulated and influenced the proliferation, migration, and invasiveness of OSCC cells. Through meRIP-seq and RNA-seq analysis, we found that METTL14 directly combined with eukaryotic translation initiation factor gamma 1 (eIF4G1) mRNA and decreased its RNA stability. According to the dual-luciferase reporter and mutagenesis assay, the mutated site 1 of exon 11 of eIF4G1 is the key target of METTL14. Knockdown of the main m6A binding protein YTHDF2 may rescue the shortened half-life of eIF4G1 mRNA induced by METTL14 overexpression. Furthermore, an in vivo tumour xenograft model confirmed that a high METTL14 expression can effectively reduce OSCC growth. Additionally, using clinical samples, we found that patients with advanced or moderately/poorly differentiated tumours exhibited lower METTL14 levels. Taken together, our results revealed that METTL14 mediated eIF4G1 expression via m6A modification and regulated autophagy levels and biological functions in OSCC. Our findings not only expand our understanding of the correlation between autophagy and RNA methylation in tumorigenesis but also present an opportunity to develop new therapeutic options.